Kemampuan Campuran Bacillus sp., Pseudomonas fluorescens, dan Trichoderma sp. untuk Mengendalikan Penyakit Layu Bakteri pada Tanaman Tomat - abdul manan; Endang Mugiastuti; Loekas Soesanto (Jurnal Fitopatologi Indonesia, 2018)
Ability of Bacillus sp., Pseudomonas fluorescens, and Trichoderma sp. to Control Tomato Bacterial Wilt DiseaseRalstonia solanacearum is known as the causal agent of bacterial wilt on tomato.  The bacteria may infect all stadia of plant growth and decrease tomato production. Biological control using antagonistic microbes is considered as a potential control alternative for the disease. This research was aimed to assay the ability of combination treatment of Bacillus sp., Pseudomonas fluorescens, and Trichoderma sp. in controlling R. solanacearum and its effect on growth and yield of tomato in the field. The treatments consisted of control (without antagonistic microbes), mixed combination of Bacillus sp. B8 + Bacillus sp. B11 + Trichoderma sp.; Bacillus sp. B8 + Pseudomonas flourescens P8 + Trichoderma sp.; and Streptomisin sulfat 20%. Antagonistic microbes was applied at planting time, as much as 100 mL per plant. The result showed that mixed combination of Bacillus sp. B8 + Bacillus sp. B11 + Trichoderma sp. was the best treatment in controlling the disease as indicated by delaying incubation period up to 6.2 days, decreasing disease incidence up to 12.3%, increasing plant growth up to 42.80%, and increasing yield up to 14.99%.